PENGARUH INDEPENDENSI DAN SKEPTISME PROFESIONAL TERHADAP KEMAMPUAN AUDITOR MENDETEKSI FRAUD: Studi Empiris Di KAP Se-Kota Bandung - Permatasari, Luh Wulan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to analyze and prove the effect of independence and professional skepticism on the auditor's ability to detect fraud. The population of this study is auditors who work in the Bandung City Public Accountant Office and the selected sample is auditors with S1 graduates and working for three years. There are 10 indicators to measure the independence variable, 15 indicators to measure professional skepticism, and 10 indicators to measure the auditor's ability to detect fraud. data that has been collected through a questionnaire and then processed using SPSS 25 with multiple linear regression analysis method. The resulting R square value is 92.3% and the sig. the independent variable and the skepticism variable are 0.000 and 0.005, respectively, so that the hypothesis is accepted. it means that the results of this study prove that the independent variable and the professional skepticism variable can increase the auditor's ability to detect fraud.